Immunophenotyping of Acute Inflammatory Exacerbations of Lung Injury Driven by Mutant Surfactant Protein-C: A Role for Inflammatory Eosinophils - Nguyen, Jacklyn; Armstrong, Brittnie S.; Cowman, Sophie; Tomer, Yaniv; Veerabhadraiah, Shivakumar R.; Beers, Michael F.; Venosa, Alessandro (Frontiers in Pharmacology, 2022)
Acute inflammatory exacerbations (AIEs) represent immune-driven deteriorations of many chronic lung conditions, including COPD, asthma, and pulmonary fibrosis (PF). The first line of therapy is represented by broad-spectrum immunomodulation. Among the several inflammatory populations mobilizing during AIEs, eosinophils have been identified as promising indicators of an active inflammatory exacerbation. To better study the eosinophil-parenchymal crosstalk during AIE-PF, this work leverages a clinically relevant model of inflammatory exacerbations triggered by inducible expression of a mutation in the alveolar epithelial type 2 cell Surfactant Protein-C gene [SP-CI73T]. Unbiased single-cell sequencing analysis of controls and SP-CI73T mutants at a time coordinated with peak eosinophilia (14 d) defined heightened inflammatory activation, chemotaxis, and survival signaling (IL-6, IL-4/13, STAT3, Glucocorticoid Receptor, mTOR, and MYC) in eosinophils. To study the impact of eosinophils in inflammatory exacerbations, the SP-CI73T line was crossed with eosinophil lineage deficient mice (GATA1Δdbl) to produce the SP-CI73TGATA1KO line. Time course analysis (7-42 d) demonstrated improved lung histology, survival, and reduced inflammation in SP-CI73TGATA1KO cohorts. Spectral flow cytometry of tissue digests confirmed eosinophil depletion in GATA1KO mice and the absence of a compensatory shift in neutrophils and immature monocyte recruitment. Eosinophil deletion resulted in progressive monocyte-derived macrophage accumulation (14 d post-injury), combined with declines in CD3+CD4+ lymphocyte and B220+ B cell abundance. Histochemical analysis revealed atypical inflammatory cell activation in SP-CI73TGATA1KO mice, with reduced numbers of Arg-1+ and iNOS+ cells, but increases in tgfb1 mRNA expression in BAL cells and tissue. Dexamethasone treatment (1 mg/kg daily, i.p.) was utilized to investigate corticosteroid efficacy in highly eosinophilic exacerbations induced by mutant SP-CI73T. Dexamethasone successfully reduced total and eosinophil (CD11b+SigF+CD11c-) counts at 14 d and was linked to reduced evidence of structural damage and perivascular infiltrate. Together, these results illustrate the deleterious role of eosinophils in inflammatory events preceding lung fibrosis and demonstrate the efficacy of corticosteroid treatment in highly eosinophilic exacerbations induced by mutant SP-CI73T.